Point mutations of the mitochondrial chaperone TRAP1 affect its functions and pro-neoplastic activity - Claudio Laquatra; Alessia Magro; Federica Guarra; Matteo Lambrughi; Lavinia Ferrone; Giulio Fracasso; Melissa Bacchin; Martina La Spina; Elisabetta Moroni; Elena Papaleo; Giorgio Colombo; Andrea Rasola (Cell Death and Disease)
Abstract The mitochondrial chaperone TRAP1 is a key regulator of cellular homeostasis and its activity has important implications in neurodegeneration, ischemia and cancer. Recent evidence has indicated that TRAP1 mutations are involved in several disorders, even though the structural basis for the impact of point mutations on TRAP1 functions has never been studied. By exploiting a modular structure-based framework and molecular dynamics simulations, we investigated the effect of five TRAP1 mutations on its structure and stability. Each mutation differentially impacts long-range interactions, intra and inter-protomer dynamics and ATPase activity. Changes in these parameters influence TRAP1 functions, as revealed by their effects on the activity of the TRAP1 interactor succinate dehydrogenase (SDH). In keeping with this, TRAP1 point mutations affect the growth and migration of aggressive sarcoma cells, and alter sensitivity to a selective TRAP1 inhibitor. Our work provides new insights on the structure-activity relationship of TRAP1, identifying crucial amino acid residues that regulate TRAP1 proteostatic functions and pro-neoplastic activity.